Hedgehog signalling does not stimulate cartilage catabolism and is inhibited by Interleukin-1β. Issue 1 (December 2015) - Thompson, Clare; Patel, Riana; Kelly, Terri-Ann; Wann, Angus; Hung, Clark; Chapple, J.; Knight, Martin
Abstract Background In osteoarthritis, chondrocytes adopt an abnormal hypertrophic morphology and upregulate the expression of the extracellular matrix-degrading enzymes, MMP-13 and ADAMTS-5. The activation of the hedgehog signalling pathway has been established in osteoarthritis and is thought to influence both of these processes. However, the role of this pathway in the initiation and progression of osteoarthritis is unclear as previous studies have been unable to isolate the effects of hedgehog pathway activation from other pathological processes. In this study we test the hypothesis that hedgehog pathway activation causes cartilage degradation in healthy cartilage and in anin vitro model of inflammatory arthritis. Methods Isolated articular chondrocytes from the bovine metacarpal-phalangeal joint were stimulated for up to 24 hours with the agonist, recombinant Indian hedgehog (r-Ihh).ADAMTS-5 andMMP-13 gene expression was quantified by real-time PCR. In addition, healthy bovine cartilage explants were treated with r-Ihh or the hedgehog antagonist, cyclopamine, and sGAG release into the media was measured over 72 hours. Studies were repeated using chondrocytes and cartilage explants from human knee joint. Finally, studies were conducted to determine the effect of hedgehog pathway activation on matrix catabolism in the presence of the pro-inflammatory cytokine, IL-1β. Results Addition of r-Ihh activated hedgehog signalling, confirmed by upregulation ofGli1 andPtch1 expression, but did not increaseADAMTS-5 orMMP-13 expression in bovine or human chondrocytes. Furthermore, r-Ihh did not induce sGAG release in healthy bovine or human cartilage explants. IL-1β treatment induced sGAG release, but this response was not altered by the stimulation or inhibition of hedgehog signalling. Hedgehog pathway activation was downregulated by IL-1β. Conversely, r-Ihh weakly suppressed IL-1β-inducedADAMTS- 5 expression. Conclusion Our results show for the first time that Indian hedgehog does not cause extracellular matrix degradation in healthyex vivo cartilage or in the presence of IL-1β and that IL-1β downregulates Indian hedgehog induced signalling. Thus, we suggest reported hedgehog induced matrix catabolism in osteoarthritis must be due to its interaction with pathological factors other than IL-1β. Hence, hedgehog signalling and its downstream effects are highly context-dependent.